On the influence of metal impurities on the electrical conductivity of the dense plasma of pulse electric discharges in water - V. V. Hladkovskyi; V. G. Panchenko; P. V. Porytskyi; O. A. Fedorovich; L. M. Voitenko; L. M. Sviata (Âderna Fìzika ta Energetika)
The effect of metal impurities on the electrical conductivity of a dense plasma of discharges in water is considered. Conductivity calculations were based on the method of Grad's moments. It is shown that a small amount of metal impurities can significantly change the value of the electrical conductivity coefficient compared to the case of pure water vapor. It was found that metal impurities can cause both an increase and a decrease in the electrical conductivity of the plasma, which is associated with the processes of interparticle collisions and the presence of clusters.